PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNINGTERHADAPHASILBELAJARSISWAKELASIVPADAMATAPELAJARANI PASDI SDINPRES 12 KABUPATEN SORONG - Julianiway; Heny Sri Astutik; Desti Rahayu (CV. ADIBA AISHA AMIRA, 2025)
Study This aims toknow InfluenceLearning model Contextual Teaching and Learningto ResultsStudy Ipas on Student ClassIVSD Inpres 12 Regency Sorong . Type study This use Study Quantitative with Design research used is One-Group Pretest-posttest design , As for Population from study This is all over participant educate Grade IV Elementary SchoolPresidential Instruction 12 Districts Sorong consisting of from Class IVA consists of 26 students , Class IVB consists of 26 students , Class IVC consists of 25 students . The technique used is random sampling . the sample used on study This is student class IV C consists of 25 students . The instrument used in the form of sheet observation And Test pg / essay . Based on results Study student Mark pretty has a mean of 67.40 whereas class control has a mean of 79.4 . From the data above can concluded that average value of each class almost The same in categoryenough .From the results test SPSS 20.0 was obtained ????ℎ ????????????????????= 4.662 and ????????????????????????= 6.708 . So that ????ℎ ????????????????????>????????????????????????And mark its significance 0.00 <0.05 . Then H 0 rejected so that can concluded that There is influence significant There is Influence Learning model Contextual Teaching and Learning to Results Study Student Class IV on Subjects IPAS in elementary school Presidential Instruction 12 Districts Push